The Production of Porous Aluminum Hydroxide Using Aluminum Nanopowder; Modern Technique and Technologies (MTT' 2005) - Godymchuk (Godimchuk) A. Yu. Anna Yuryevna; Ilyin A. P. Aleksandr Petrovich; An V. V. Vladimir Vilorievich; Astankova A. P. Anna Petrovna (2005, 2005)
Title screen